Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter R - Algebra Reference - R.1 Polynomials - R.1 Exercises: 21

Answer

$(x+1)(x+2)(x+3)=x^{3}+6x^{2}+11x+6$

Work Step by Step

$(x+1)(x+2)(x+3)$ First, evaluate only $(x+1)(x+2)$ and simplify: $(x+1)(x+2)(x+3)=(x^{2}+2x+x+2)(x+3)=...$ $...=(x^{2}+3x+2)(x+3)=...$ Now, evaluate $(x^{2}+3x+2)(x+3)$ and simplify again: $...=x^{3}+3x^{2}+3x^{2}+9x+2x+6=...$ $...=x^{3}+6x^{2}+11x+6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.